Genetic evaluation of growth performance of Rambouillet sheep in Jammu and Kashmir, India - NUSRAT NABI KHAN; MUBASHIR A RATHER; A HAMADANI; DIBYENDU CHAKRABORTY (Indian Journal of Animal Sciences, 2022)
The present study was conducted to genetically evaluate the growth performance in Rambouillet sheep. For this, data of 7,158 lambs born to 181 sires over a 16 year period from 2000 to 2015 were collected from Government Sheep Breeding Farm, Reasi, India. Random effect of sire as well as fixed effects of sex, genetic group, year, parity and birth type on the performance of this breed were evaluated. Ten traits were taken into consideration, viz. birth weight (BW), weaning-weight (WW), 6 months body weight (SMW), 12 month weight (YBW), average daily gain (birth to weaning) (ADG-1), metabolic mass at weaning age (WW0.75), Kleiber ratio (birth to weaning) (KR-1), average daily gain (weaning to yearling age) (ADG-2), and metabolic mass at 12 months (YBW0.75) and Kleiber ratio (weaning to 12 months) (KR-2). The overall least-squares means for BW, WW, SMW, YBW, ADG-1, WW0.75, KR-1, KR-2, ADG-2, and YBW0.75 were 3.16±0.05 kg, 13.79±0.16 kg, 18.81±0.22 kg, 28.00±0.26 kg, 116.93±1.72 g/day, 7.13±0.06 kg, 16.22±0.11, 4.38±0.10, 53.95±1.36 g/day, and 12.14±0.08 kg respectively. The sire and year effects of birth were significant. The genetic group was a non-significant source of variation for all traits under study. Sex effect was significant on most traits under study. Heritability ranged from low to moderate. Genetic and phenotypic correlations also ranged from low to very high. Genetic, phenotypic and environmental trends for BW, WW and WW0.75, genetic trends for BW, WW, SMW and WW0.75 and environmental trends for YBW, YBW0.75 and KR-2 were negative. Our results indicate that most of the variation may be attributed to nonadditive genetic effects and may also be influenced by the environment.